The Challenges of Implementing the Online Single Submission (OSS) System in Business Licensing (NIB) and Halal Certification Processes - Rafianti, Fitri; Nurhayati, Siti; Wakhyuni, Emi; Andafi, Muhammad (Faculty of Law, Universitas Pekalongan, 2024)
This article examines the implementation of the Online Single Submission (OSS) system in business licensing in Indonesia, particularly concerning Business Identification Numbers (NIB) and halal certification. OSS, designed to streamline the licensing process electronically, aims to improve efficiency and accessibility in public services supporting business activities. However, this study finds that in practice, the OSS system encounters multiple challenges, both technical and regulatory. Key issues identified include limited technological access for micro and small business operators, unclear regulatory standards, and concerns regarding data security and information management. Additionally, OSS presents difficulties in the halal certification process, such as complex criteria and the need for accurate data verification. The government is encouraged to take adaptive steps, including enhancing transparency, simplifying bureaucratic procedures, and providing technical support for business operators. These adjustments are anticipated to optimize the OSS system, fostering a better investment climate and increasing the competitiveness of SMEs in Indonesia. This research adopts a normative juridical approach with qualitative analysis based on primary, secondary, and tertiary legal sources. The study’s findings recommend that the government be more responsive to the challenges faced by business operators to realize an inclusive and effective OSS system